Application of Bamboo and Oil Palm Clinker in Lightweight Reinforced Concrete Beams - Kamaruddin, Rezuwan (1991)
This study presents the results of the structural properties of light weight oil palm clinker concrete beams reinforced with bamboo. The variables used in case of light weight concrete were water - cement ratio and mix proportion. The hardened concrete was tested for compressive strength, tensile strength, modulus of elasticity, shrinkage and creep. So far as the reinforcement is concerned the results of mechanical and physical properties of Dendrocal amusasper bamboointerms of specific gravity, moisture content, tensile strength of nodal and internodal specimens, compression strength parallel and perpendicular to the grain, static bending test and modulus of elasticity are presented. Twelve beams with different reinforce mentratios were casted and tested under the two - third point loading to obtain service load, propagation of cracks, deflection, mode of failure and the failure loads. Four of these beams are light weight oil palm clinker concretere inforced with split bamboo and another four beams are reinforced with steel while the restare normal concrete beams reinforced with split bamboo. Reinforcement percentages of 0.5, 1.0, 1.5 and 2.0 were tried in these experiments.Based on the strength of properties obtained, it can be concluded that the selected bamboo species can be used as reinforcement in concrete while oil palm clinker concrete is comparable to those of the control normal concrete specimen. Of the twelve beams tested, it was found that the composite action of oil palm clinker concrete and bamboo reinforcement is reasonably exhibited. The British Standards Code of Practice BS8ll0 could be used in designing the light weight clinker concrete beams reinforced with bamboo. In conclusion, clinker concrete beams reinforced with split bamboo as main reinforcement and as stirrups can be viable so long as the durability of the biological material is ensured.